Psychiatrie itinérante à Cotonou au Bénin - GANSOU, MAGLOIRE GRÉGOIRE; TOGNIDE, MATHIEU COOVI; FIOSSI-KPADONOU, EMILIE ABLAWA; SALIFOU, S.; EZIN-HOUNGBE, JOSIANE IRMA. A; AGOSSOU, THÉRÈSE ANTOINETTE. A. (My University, 2011)
.................
Keywords: Psychiatrie; Cotonou